Challenges of Promoting Sustainable Mobility on University Campuses: The Case of Eastern Mediterranean University - Dehghanmongabadi, Abolfazl; Hoskara, Sebnem (Mdpi, 2018)
Universities have the extraordinary ability to generate awareness regarding all aspects of sustainability in communities. To be successful, they must first adopt and model sustainable concepts within their own campuses. Transportation is one of the most affective sectors on the level of sustainability on university campuses. In recent decades, numerous universities around the world have begun encouraging usage of active modes of transportation through various strategies. This research has a multi-faceted approach to researching proven strategies, sampling local conditions, and making context-driven recommendations. The literature review outlines the most effective strategies related to Transportation Demand Management (TDM) for promoting usage of active modes of transportation inside university campuses. After that, the condition of existing facilities and strategies as well as commuters' propensities related to active modes of transportation in the Eastern Mediterranean University (EMU) campus are evaluated using both qualitative and quantitative methods. The results include a set of recommendations and a framework for administrating, implementing, and enhancing a sustainable transportation system thereby increasing the commuter's use of sustainable active modes of transportation to, from, and within the university campus.
Keywords: sustainability; transportation; sustainable modes of transportation; university campus; EMU